The Role of Various Salt Concentrations on Total Microbial Count (TPC) and Histamine in Shrimp Paste (Acetes sp.): Peran Berbagai Konsentrasi Garam Terhadap Total Mikroba (ALT) dan Histamin Pada Terasi Udang Rebon (Acetes sp). - Sri Rumiyati; Niken Prawesti Listyaningrum (Universitas Muhammadiyah Sidoarjo, 2026)
Shrimp paste (terasi) made from rebon shrimp (Acetes sp.) is a traditional Indonesian fermented product that poses food safety risks related to pathogenic microbial growth and histamine formation. This study aims to examine the role of salt in controlling total microbial counts and histamine levels in rebon shrimp paste. The study employed a Completely Randomized Design (CRD) with three salt concentration treatments (5%, 10%, and 15%) and three replications. The parameters tested included moisture content, Total Plate Count (TPC), and histamine levels. The shrimp paste was fermented for 30 days at room temperature. The results showed that increasing salt concentration had a significant effect (p<0.05) on reducing moisture content. Salt concentrations of 5%, 10%, and 15% resulted in moisture contents of 33.65±0.09%, 32.82±0.04%, and 29.68±0.07%, respectively, all of which comply with SNI 2716:2016 (maximum 35%). TPC values across all treatments were very low (<250 CFU/g), well below the SNI maximum limit of 1 x 105 CFU/g. Histamine levels in all treatments were not detected (<1.35 mg/kg), indicating excellent product safety compared to international standards (FDA 50 mg/kg, SNI for fresh fish 100 mg/kg). Salt effectively controls microbes through the mechanism of reducing water activity and osmotic pressure, as well as inhibiting histamine-forming bacteria. This research demonstrates that salt concentrations of 5-15% with a 30-day fermentation period produce rebon shrimp paste that meets national quality and food safety standards. Salt concentration 15% is recommended for optimal shelf life.